High Performance Air Breathing Flexible Lithium–Air Battery. Issue 42 (16th September 2021) - Jaradat, Ahmad; Zhang, Chengji; Singh, Sachin Kumar; Ahmed, Junaid; Ahmadiparidari, Alireza; Majidi, Leily; Rastegar, Sina; Hemmat, Zahra; Wang, Shuxi; Ngo, Anh T.; Curtiss, Larry A.; Daly, Matthew; et al.
Abstract: Lithium–oxygen (Li–O2 ) batteries possess the highest theoretical energy density (3500 Wh kg −1 ), which makes them attractive candidates for modern electronics and transportation applications. In this work, an inexpensive, flexible, and wearable Li–O2 battery based on the bifunctional redox mediator of InBr3, MoS2 cathode catalyst, and Fomblin‐based oxygen permeable membrane that enable long‐cycle‐life operation of the battery in pure oxygen, dry air, and ambient air is designed, fabricated, and tested. The battery operates in ambient air with an open system air‐breathing architecture and exhibits excellent cycling up to 240 at the high current density of 1 A g −1 with a relative humidity of 75%. The electrochemical performance of the battery including deep‐discharge capacity, and rate capability remains almost identical after 1000 cycle in a bending fatigue test. This finding opens a new direction for utilizing high performance Li–O2 batteries for applications in the field of flexible and wearable electronics. Abstract : An air‐breathing sheet‐type flexible Li–O2 battery operating under oxygen, dry and ambient air is developed. The battery shows an excellent performance (up to 370 cycles) under a high current density of 1 A g –1 . The electrochemical performance of the battery including deep‐discharge capacity and rate capability remains almost identical after 1000 cycle in a bending fatigue test.